A new species of the genus Capsus Fabricius (Hemiptera: Heteroptera: Miridae: Mirinae) from the Korean Peninsula, with a key to the Korean Capsus species - Kim, Junggon; Park, Haechul; Heiss, Ernst; Jung, Sunghoon (Zootaxa, 2015)
A new species of the genus Capsus Fabricius (Hemiptera: Heteroptera: Miridae: Mirinae) from the Korean Peninsula is reported, and congeners in the Korean Peninsula are reviewed. Biological information such as host plants and distributions with a key to the Korean species are also provided.